Assessment of Neuropsychological Late Effects in Survivors of Childhood Leukemia. (1st March 2014) - Kalafatçılar, Ayşe İpek; Tüfekçi, Özlem; Ören, Hale; Hız, Semra; Güleryüz, Handan; Akay, Aynur; Orçim, Esmahan; Olgun, Yüksel; İrken, Gülersu
<x xml:space="preserve">Abstract</x> The neurologic dysfunctions caused by treatment may affect health and quality of life in survivors of childhood leukemia. The objective of this study was to identify the neuropsychological late effects of leukemia treatment to provide an assessment about the degree and incidence of these late effects. Neurological and ophtalmological examination, cranial magnetic resonance imaging (MRI), auditory and neurocognitive tests, and questionnaires of quality of life were performed to 44 acute leukemia survivors at least 5 years after diagnosis. Median time since completion of chemotherapy was 7.5 years (2–18) and median age at the time of the study was 16.4 years (8–31). At least one or more late effects detected by physical examination (PE), neurological tests, or neurocognitive tests encountered in 80% of the patients, and 64% of the patients specified at least one complaint in the quality of life questionnaire. MRI revealed pathological findings in 18% and electroencephalogram (EEG) abnormalities were present in 9% of the patients. Evaluation of total intelligence scores revealed that 30% of patients' IQ scores were <80 and 70% of the patients' scores demonstrated neurocognitive dysfunctions. The patients >6 years at the time of diagnosis were found to have more psychological problems and higher rates of smoking and alcohol consumption. The most frequent complaint was headache and the most common problem in school was denoted as difficulty in concentration. Our study demonstrated that most of the survivors of childhood leukemia are at risk of developing neuropsycological late effects.